The Effect of Work-Life Balance on Work Motivation of Members of the South Sulawesi Provincial DPRD - Tri Kurniawan; Andi Mustika Amin; Tenri Sayu Puspitaningsih Dipoatmodjo; Zainal Ruma; Uhud Darmawan Natsir (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine the effect of work-life balance on the work motivation of members of the South Sulawesi Provincial DPRD. The research employs a quantitative method to analyze data and seeks to explain the reciprocal influence between the variables under investigation. The results indicate that work-life balance (X) has a positive and significant effect on work motivation (Y) among DPRD members in South Sulawesi. The research instruments used were declared valid and reliable, making them trustworthy for measuring both work-life balance and work motivation. The simple regression analysis shows that the higher the level of work-life balance, the higher the work motivation of DPRD members. This implies that when members are able to maintain a balance between their work responsibilities and personal life, they tend to feel more enthusiastic, focused, and responsible in carrying out their legislative duties. Conversely, disruptions in the balance between work and personal life tend to decrease work motivation. It is recommended that factors supporting the work-life balance of DPRD members be considered, such as implementing a more structured session schedule, providing sufficient rest periods, and supporting both physical and mental health. By maintaining this balance between personal and professional life, work motivation among DPRD members can be enhanced.